Crystal structure of calcium dinickel(II) iron(III) tris(orthophosphate): CaNi(2)Fe(PO(4))(3) - Ouaatta, Said (International Union of Crystallography, 2017)

(untitled) (Acta Crystallogr E Crystallogr Commun)
The title compound, CaNi(2)Fe(PO(4))(3), was synthesized by solid-state reactions. Its structure is closely related to that of α-CrPO(4) in the space group Imma. Except for two O atoms in general positions, all atoms are located in special positions. The three-dimensional framework is built up from two types of sheets extending parallel to (100). The first sheet is made up from two edge-sharing [NiO(6)] octahedra, leading to the formation of [Ni(2)O(10)] double octahedra that are connected to two PO(4) tetrahedra through a common edge and corners. The second sheet results from rows of corner-sharing [FeO(6)] octahedra and PO(4) tetrahedra forming an infinite linear chain. These layers are linked together through common corners of PO(4) tetrahedra and [FeO(6)] octahedra, resulting in an open three-dimensional framework that delimits two types of channels parallel to [100] and [010] in which the eightfold-coordinated Ca(II) cations are located.